2014
DOI: 10.1161/circep.114.001506
|View full text |Cite
|
Sign up to set email alerts
|

Resumption of Chest Compressions After Successful Defibrillation and Risk for Recurrence of Ventricular Fibrillation in Out-of-Hospital Cardiac Arrest

Abstract: Background-Prior investigation of out-of-hospital cardiac arrest has raised the concern that ventricular fibrillation (VF) recurrence may be triggered by chest compression (CC) resumption. We investigated predictors of VF recurrence after defibrillation, including timing of CC resumption. Methods and Results-Patients with witnessed out-of-hospital cardiac arrest and initial rhythm of VF from an Utstein-style database were analyzed. For each shock that defibrillated VF, CC resumption and VF recurrence times w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…97 Another study of patients presenting in VF after a witnessed arrest concluded that recurrence of VF within 30 seconds of a shock was not affected by the timing of resumption of chest compressions. 98 Thus, the effect of chest compressions on recurrent VF is not clear. It is likely that in the future, algorithms that recognize recurrent VF during chest compressions with high sensitivity and specificity will allow us to deliver a shock earlier in the CPR cycle, thereby reducing the length of time the myocardium is fibrillating and the duration of postshock CPR.…”
Section: Evidence Summarymentioning
confidence: 99%
“…97 Another study of patients presenting in VF after a witnessed arrest concluded that recurrence of VF within 30 seconds of a shock was not affected by the timing of resumption of chest compressions. 98 Thus, the effect of chest compressions on recurrent VF is not clear. It is likely that in the future, algorithms that recognize recurrent VF during chest compressions with high sensitivity and specificity will allow us to deliver a shock earlier in the CPR cycle, thereby reducing the length of time the myocardium is fibrillating and the duration of postshock CPR.…”
Section: Evidence Summarymentioning
confidence: 99%
“…334 If a shock has been successful immediate resumption of chest compressions does not increase the risk of VF recurrence. 335 Furthermore, the delay in trying to palpate a pulse will further compromise the myocardium if a perfusing rhythm has not been restored. 336 • Continue CPR for 2 min, then pause briefly to assess the rhythm; if still VF/pVT, give a second shock (150-360 J biphasic).…”
Section: Shockable Rhythms (Ventricular Fibrillation/pulseless Ventrimentioning
confidence: 99%
“…Chest compression rates did not significantly differ between the two groups. The time from connection of the AED to first shock was significantly shorter in the control group than the experimental group (experimental: 34 [31-38] s vs. control: 21 [19][20][21][22][23][24] s; P < 0.001), due to the introduction of 15 s of CPR before in shock in the experimental protocol. The per-protocol analysis showed comparable results for the secondary outcomes (Supplemental Table 3).…”
Section: Secondary Outcomesmentioning
confidence: 99%